Assessing the Environmental Drivers of Lassa Fever in West Africa: A Systematic Review - Natalie A. Davis; Madeline A. Kenyon; Bruno M. Ghersi; Jessica L. Decker Sparks; Jonathon D. Gass (Viruses)
The spread of Lassa virus in West Africa is reliant on the abundance and distribution of its rodent host reservoirs. While the impact of environmental change on viral spread has been studied for many zoonotic viruses, there is still a limited understanding of how seasonal impacts, land-use conversion, and biodiversity loss influence the expansion of Lassa virus among reservoirs. This systematic review synthesizes existing research on the association between environmental variables and Lassa virus circulation in West Africa to inform future research, public health interventions, and One Health policy. We searched international and African scientific databases using a set of pre-defined search terms to obtain publications reporting on Lassa virus in West Africa between 1969 and 2023. A total of 9465 articles were retrieved from this search and 70 studies met inclusion criteria for this review. Through systematic data extraction, we identified seasonal precipitation, land-use change, and host expansion as key environmental drivers of Lassa virus in reservoir hosts; however, we also highlight notable gaps in knowledge that limit our current understanding of these complex relationships. This review underscores the need for interdisciplinary research and strategies to mitigate the impacts of environmental change on Lassa virus transmission and protect vulnerable populations in West Africa.